2023
DOI: 10.1021/acsnano.3c02103
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Photoluminescence Mediated by Sulfur Vacancies in 2D Molybdenum Disulfide

Yiru Zhu,
Juhwan Lim,
Zhepeng Zhang
et al.

Abstract: Atomic defects in monolayer transition metal dichalcogenides (TMDs) such as chalcogen vacancies significantly affect their properties. In this work, we provide a reproducible and facile strategy to rationally induce chalcogen vacancies in monolayer MoS 2 by annealing at 600 °C in an argon/hydrogen (95%/5%) atmosphere. Synchrotron Xray photoelectron spectroscopy shows that a Mo 3d 5/2 core peak at 230.1 eV emerges in the annealed MoS 2 associated with nonstoichiometric MoS x (0 < x < 2), and Raman spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…To further understand the role of defects in determining the growth morphology of metal films on 2D surfaces, we deposited In and Au on thermally annealed MoS 2 with additional defects . For In, the additional defects increase the nucleation density by 50%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further understand the role of defects in determining the growth morphology of metal films on 2D surfaces, we deposited In and Au on thermally annealed MoS 2 with additional defects . For In, the additional defects increase the nucleation density by 50%.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the relatively high diffusivity 3.65 × 10 To further understand the role of defects in determining the growth morphology of metal films on 2D surfaces, we deposited In and Au on thermally annealed MoS 2 with additional defects. 35 For In, the additional defects increase the nucleation density by 50%. However, the nucleation density for Au on defective MoS 2 is similar to what was observed on pristine MoS 2 , as the nucleation of Au is dominated by defects created on the MoS 2 surface during the deposition process (see Section 5 in the SI).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Defects are thought to have a significant effect on excitons and their complexes in TMDs . A significant amount of ongoing research is dedicated for tailoring the properties of MoS 2 through defect engineering using various techniques, including plasma treatment, hot electron doping, ion beam irradiation, superacid treatment, strain engineering, thermochemical treatment, etc. It has been observed that sulfur (S) vacancy-related defects and their passivation have the most crucial effect on optical and electrical properties in MoS 2 . , Recently, Zhu et al have reported sub-band gap photoluminescence (PL) emission related to S vacancy in mechanically exfoliated MoS 2 by annealing in different ambience, while Bretscher et al have improved the PL emission and mobility of exfoliated MoS 2 using chemical passivation of S vacancy . During chemical vapor deposition (CVD) of a MoS 2 film, incorporation of H 2 in the growth environment along with the carrier gas, Ar, can serve as an effective approach to engineer the S vacancy-related defects in the MoS 2 film.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial discovery of graphene, interest in two-dimensional (2D) layered materials has significantly intensified. These materials display distinct electrical, thermal, magnetic, and optical characteristics, rendering them attractive for diverse applications, such as nanophotonics, nanodevices, sensing, and catalysis. The physical and chemical attributes of 2D materials can be engineered through doping, , introduction of defects, , incorporation into composites, and exposure to external electric fields, thereby greatly enhancing their practical application potential. Surface-enhanced Raman scattering (SERS) is a highly sensitive molecular spectroscopic technique that provides structural insights into substances.…”
Section: Introductionmentioning
confidence: 99%